On the common point spectrum of pairs of self-adjoint extensions - Posilicano, A. (Methods of Functional Analysis and Topology, 2014)
Given two different self-adjoint extensions of the same symmetric operator, we analyse the intersection of their point spectra. Some simple examples are provided.